Changes in public awareness of the social determinants of health over 15 years in Wisconsin, United States - Stephanie A. Robert; Amy Yinan Liu (Preventive Medicine Reports)
Objective: To investigate 15-year changes in public awareness of the social determinants of health (SDoH) between 2007 and 2023. Methods: A 2007 survey of 1172 Wisconsin, U.S. adults is compared to a 2023 survey of 1631 Wisconsin adults. In both surveys, respondents were asked to rate 16 factors regarding how strongly each impacts health. Regression analyses examine how demographic factors differentiate responses in both survey years. Results: In both 2007 and 2023, the four most highly rated factors affecting health were: personal health practices, stress, health insurance, and access to affordable health care. Between 2007 and 2023, there was little or no increase, and even some decrease, in endorsement of many social determinants of health like income, education, housing, and social support. Older adults, women, and those with lower income were generally more likely to endorse the SDoH in both years. Party identification was the demographic factor that most strongly differentiated responses, with Democrats rating more highly many of the social determinants of health than either Republicans or Independents in both years. This differentiation by party identification was even stronger in 2023 than 2007. Conclusions: Despite consistent research documenting the social determinants of health, growing health care and policy attention to the social determinants of health, and population exposure to a variety of social determinants during the COVID-19 pandemic, there is little or no increase in public recognition of the social determinants of health, and notable increasing partisan divides.